Cardiac biomarkers as sensitive tools to evaluate the impact of xenobiotics on amphibians: the effects of anionic surfactant linear alkylbenzene sulfonate (LAS) - Jones-Costa, Monica; Franco-Belussi, Lilian [UNESP]; Vidal, Felipe Augusto Pinto; Gongora, Nathália Penteado; Castanho, Luciano Mendes; dos Santos Carvalho, Cleoni; Silva-Zacarin, Elaine Cristina Mathias; Abdalla, Fabio Camargo; Duarte, Iolanda Cristina Silveira; Oliveira, Classius De [UNESP]; de Oliveira, Cristiane Ronchi [UNESP]; Salla, Raquel Fernanda (Elsevier, 2018)
Amphibian populations have been experiencing a drastic decline worldwide. Aquatic contaminants are among the main factors responsible for this decline, especially in the aquatic environment. The linear alkylbenzene sulfonate (LAS) is of particular concern, since it represents 84% of the anionic surfactants’ trade. In Brazil, the maximal LAS concentration allowed in fresh waters is 0.5 mg L−1, but its potential harmful effects in amphibians remain unknown. Therefore, this study aimed to analyze the effects of a sublethal concentration of LAS (0.5 mg L−1) for 96 h on sensitive cardiac biomarkers of bullfrog tadpoles, Lithobates catesbeianus (Shaw, 1802). For this, we measured the activity level (AL - % of animals), in situ heart rate (fH - bpm), relative ventricular mass (RVM - % of body mass), in vitro myocardial contractility and cardiac histology of the ventricles. Tadpoles’ AL and fH decreased in LAS group. In contrast, the RVM increased, as a result of a hypertrophy of the myocardium, which was corroborated by the enlargement of the nuclear measures and the increase of myocytes’ diameters. These cellular effects resulted in an elevation of the in vitro contractile force of ventricle strips. Acceleration in the contraction (TPT - ms) also occurred, although no alterations in the time to relaxation (THR -ms) were observed. Therefore, it can be concluded that even when exposed to an environmentally safe concentration, this surfactant promotes several alterations in the cardiac function of bullfrog tadpoles that can impair their development, making them more susceptible to predators and less competitive in terms of reproduction success. Thus, LAS concentrations that are considered safe by Brazilian by regulatory agencies must be revised in order to minimize a drastic impact over amphibian populations. This study demonstrates the relevance of employing cardiac biomarkers at different levels (e.g., morphological, physiological and cellular) to evaluate effects of xenobiotics in tadpoles.
Keywords: Anurans; Cardiac function, ecotoxicology; Heart; Pollutant